2020
DOI: 10.3390/ijms21145102
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CXCL4 Antibody Reactivity Is Present in Systemic Sclerosis (SSc) and Correlates with the SSc Type I Interferon Signature

Abstract: Systemic sclerosis (SSc) is characterized by skin/internal organ fibrosis, vasculopathy and autoimmunity. Chemokine (C-X-C motif) ligand 4 (CXCL4) is an SSc biomarker, predicting unfavorable prognosis and lung fibrosis. CXCL4 binds DNA/RNA and favors interferon (IFN)-α production by plasmacytoid dendritic cells (pDCs), contributing to the type I IFN (IFN-I) signature in SSc patients. However, whether CXCL4 is an autoantigen in SSc is unknown. Here, we show that at least half of SSc patients show consistent ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 42 publications
6
39
0
Order By: Relevance
“…(See Table 1, for SSc patients, VEDOSS patients, and control HD studied). In keeping with previously published work, anti-CXCL4-autoantibody reactivity was detectable in SSc and not in HD (Figure 1a) [15]. SSc subtype analysis indicated that anti-CXCL4 autoantibodies were present in both eaSSc and lsSSc.…”
Section: Ssc and Vedoss Can Share Autoantibody Specificitysupporting
confidence: 91%
See 4 more Smart Citations
“…(See Table 1, for SSc patients, VEDOSS patients, and control HD studied). In keeping with previously published work, anti-CXCL4-autoantibody reactivity was detectable in SSc and not in HD (Figure 1a) [15]. SSc subtype analysis indicated that anti-CXCL4 autoantibodies were present in both eaSSc and lsSSc.…”
Section: Ssc and Vedoss Can Share Autoantibody Specificitysupporting
confidence: 91%
“…In contrast, the eaSSc patients with pitting scars were characterized by lower anti-CXCL4 antibody reactivity, as compared to those with no pitting scars (Figure S3). These results suggest that anti-CXCL4 autoantibodies in lsSSc, but not in eaSSc, may be markers of skin inflammation, in addition to being associated with lung fibrosis, as previously reported [15]. The results seem also suggest that anti-CXCL4-, and possibly anti-CXCL4-L1-autoantibodies, may acquire pathogenic functions in the skin inflammation and lung fibrosis at late SSc-phases.…”
Section: Anti-cxcl4 Autoantibodies Can Be Associated With Skin Involvement In Lssscsupporting
confidence: 83%
See 3 more Smart Citations